Jogja Smart Service as a Digital Public Services: Based on Agile Governance Perspective - Bagaskoro Nur Abu Yogar; Dyah Mutiarin; Muhammad Noor Cahyadi Eko Saputro (LPPMPK - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
Jogja Smart Service (JSS) is a digital-based public service innovation created by the Yogyakarta city government, the purpose of creating Jogja Smart Service (JSS) is to meet the needs of the public service sector to the citizens of Yogyakarta which was driven by the high number of Covid-19 cases in Yogyakarta at that time, this forced the city government to continue to provide services to the community even amid a pandemic. This research aims to test the theory of Agile Governance developed by Kruchten to innovate digital-based public services Jogja Smart Service (JSS). Researchers will test 3 indicators contained in the theory of Agile Governance against Jogja Smart Service (JSS), namely indicators: 1) Based on Quick Wins, which will assess Jogja Smart Service (JSS) in terms of speed and accuracy. 2) Systematic and Adaptive Approach, which will assess systematic and adaptive aspects. 3) Simple Design and Continuous Refinement which will assess the aspects of the ability of the Yogyakarta city government to develop Jogja Smart Service (JSS)